Exchange of inherited property at Elephantine (Cowley 1) - Porten, Bezalel 1931-; Szubin, H. Z. (1982)
Utilizing a new approach in comparative legal studies, that we formerly employed in the reconstruction of legal realia in Jewish Law, this article seeks to reconstruct a hitherto unrecognized legal institution in Elephantine, i.e., probate. Specifically, the article reinterprets and redefines the terms mntʾ, yhb, mtʾ and mhḥsn with a keen eye to the legal nuances conveyed in the context of this document (Cowley 1) and other cognate legal texts.